ANALISIS SIKAP ILMIAH DALAM BUKU CONFIDENCE IN SCIENCE: KAPAN BULAN BERUBAH BENTUK? - desty putri (Rihlah Review: Jurnal Pendidikan Islam, 2024)
The purpose of this study is to examine the integration of scientific concepts with the development of scientific attitudes and moral internalization through a narrative approach in the Confidence in Science reference book, entitled "When Does the Moon Change Shape?" Confidence in Science is a reference book from Korea that has been translated into Indonesian. The book comprises 40 titles, each addressing a distinct scientific theme. Confidence in Science is presented in three formats: narratives, encyclopedias, and comics. This research employs a library research methodology, with the book Confidence in Science, entitled "When Does the Moon Change Shape?" serving as the object of investigation. The research instruments include data cards and checklist sheets with data analysis techniques employing content analysis. The findings of this study indicate that the book in question is effective in conveying astronomical concepts in an engaging and accessible manner for children. Furthermore, this book is effective in instilling a range of scientific attitudes, including curiosity, objectivity, thoroughness, skepticism, cooperation, self-confidence, and concern for facts. Another significant aspect is the book's contribution to children's moral development through the illustration of ethical reasoning in a scientific context. A holistic approach that integrates scientific knowledge with character development is particularly well-suited to the developmental needs of elementary school-aged children. It is recommended that a similar approach be employed in the development of science teaching materials for children, with an emphasis on the integration of cognitive and moral aspects in the learning process.